Hubungan Vertical Jump dengan Jump Shoot Pada Permainan Bola Basket Grup Megic Kid Lubuklinggau - Bimo Sepra Winata (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine whether there is a relationship between vertical jump and jump shot in the basketball game of the magic kid Lubuk linggau group. The research method used is descriptive, and the type of research is correlation analysis. The sample in this study was the Magic Kid Lubuk linggau Putra group, with as many as10 people. The data collection technique in this study was a test. The data analysis technique used the following steps: normality, homogeneity, and correlation test. The instruments used in this study were the vertical jump test and the jump shot into the ring for one minute. The results of statistic analysis from multiple correlation analysis obtained dan F-count of 0.1262, with a significance level of 5%, an F-table of 0.632 was obtained. It turns out that F-count 0.1262 is smaller than F-table 0.632, meaning no significant relationship between vertical jump and jump shoot in basketball games. The results showed no significant relationship between vertical jump and jumped shot in the basketball game of theme Magic Kid Lubuklinggau group Keywords: Basket Ball, Jump Shoot, Relationship, Vertical Jump,